2015
DOI: 10.1016/j.jvir.2015.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Bariatric Embolization of the Gastric Arteries for the Treatment of Obesity

Abstract: Obesity is a public health epidemic in the United States, which results in significant morbidity, mortality, and cost to the healthcare system. Despite advancements in therapeutic options for the bariatric patients, the number of overweight and obese individuals continues to rise. Thus, complimentary or alternative treatments to lifestyle changes and surgery are urgently needed. Embolization of the left gastric artery, or ‘bariatric arterial embolization’, has been shown to modulate body weight in animal model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 53 publications
0
20
0
2
Order By: Relevance
“…Leptin levels in circulation increase with presence of obesity and decrease with weight loss (25). Plasma levels of leptin increase during and after eating (26). In a study conducted by Kalinowski et al (9), leptin levels decreased significantly 1 month after surgery and continued to decrease at 6 and 12 months after LSG.…”
Section: Discussionmentioning
confidence: 98%
“…Leptin levels in circulation increase with presence of obesity and decrease with weight loss (25). Plasma levels of leptin increase during and after eating (26). In a study conducted by Kalinowski et al (9), leptin levels decreased significantly 1 month after surgery and continued to decrease at 6 and 12 months after LSG.…”
Section: Discussionmentioning
confidence: 98%
“…Leptin is a hormone that is mainly produced by adipocytes; it promotes energy expenditure and reduces hepatic gluconeogenesis and insulin resistance [12]. Plasma levels of leptin increase during and after eating [13]. Studies have shown that ghrelin and leptin levels decrease after bariatric surgery [14].…”
Section: Introductionmentioning
confidence: 99%
“…Despite advances in medical research and surgical techniques, obesity remains one of the largest drivers of chronic disease and healthcare costs in the United States (2,3). In response to the growing obesity epidemic, left gastric artery (LGA) embolization has evolved as a promising procedure for weight loss therapy (4,5).…”
mentioning
confidence: 99%
“…LGA embolization has been shown to suppress serum ghrelin levels and modulate weight in animal models (4,5,7). Promising results in animal models prompted investigators to retrospectively evaluate patients who underwent LGA embolization, an established procedure in interventional radiology for treatment of gastrointestinal (GI) bleeding.…”
mentioning
confidence: 99%
See 1 more Smart Citation